Mathematics Learning Video Media for Sixth Grade Elementary School - Ni Luh Putu Putri Priantini Dewi; Gusti Ngurah Sastra Agustika (Universitas Pendidikan Ganesha, 2022)
Lacked use of instructional media in primary school impacted the quality of students learning outcomes. Based on the problem, this study is aimed to develop media in developing mathematics learning video media based on a contextual approach to improve the learning outcomes of elementary school students. These video media were developed by using ASSURE is consisted of 6 stages, namely: Analyze, State, Select, Utilize, Require, and Evaluate. The data that had been collected are qualitative and quantitative. Data were collected by using the method of observation, interviews, document recording, and questionnaires. Video media validity has been measured through testing content experts, instructional design experts, instructional media experts, and individual trials. The results of the study show that: (a) the results of the review of the learning content experts have very good qualifications with a percentage (91.66%), the results of the reviews of learning design experts have very good qualifications with a percentage (92.50%), (c) the results of expert reviews learning media showed that video media was good with a percentage (93.33%), and (d) individual test results showed that video media was very good with a percentage (93.17%). Based on the results of this study, developing mathematics learning video media based on a contextual approach to improve learning outcomes by using the ASSURE model on the subject of surface area and volume of class VI blocks shows very good qualifications. It is suitable for use in elementary schools.